Getting published in international journals: Perception of Indonesian scholars in linguistics and language education on the issues they face - Zifirdaus Adnan; Bambang Kaswanti Purwo (UNIB Press, 2023)
Publishing research articles (RAs) in international journals (IJs) has been considered increasingly crucial by developing countries including Indonesia. For the Indonesian Government, publishing RAs in international journals is important to increase its competitive power academically as Indonesian universities are entering a global competition to attract students. Therefore, publishing RAs in international journals is becoming more and more important, e.g. for promotion, especially at senior levels. This study reports on the second and most widespread national-level survey of a three-year project funded by the former Indonesian Government through its Ministry of Research and Higher Education (MRHE). The central question is,